Quality of comprehensive assessment among severely ill TB patients referred after triaging in southern India - H. D. Shewade; A. Frederick; S. Kiran Pradeep; T. Daniel Rajasekar; G. Kiruthika; T. Bhatnagar; K. V. Suma; P. Ravichandran; K. Gayathri; R. Vijayaprabha; D. P. Pathinathan; D. Chidambaram; et al. (Public Health Action, 2024)
To reduce TB deaths, Tamil Nadu, a southern Indian state, implemented the first state-wide differentiated TB care strategy starting April 2022. Triage-positive severely ill patients are prioritised for comprehensive assessment and inpatient care. Routine program data during October–December 2022 revealed that documentation of total score after comprehensive assessment was available in only 39%, possibly indicating poor quality of comprehensive assessment. We confirmed this using operational research. The case record form to record comprehensive assessment was used only in 26% and among these, the completeness and correctness in filling out the form were sub-optimal. There is a clear need to enhance the quality of comprehensive assessments.